2023
DOI: 10.1152/ajpheart.00057.2023
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes prolong ventricular repolarization in people who smoke tobacco cigarettes: implications for harm reduction

Abstract: Electronic cigarettes are often used for smoking cessation as a harm reduction strategy, but studies comparing risks of electronic cigarettes (ECs) and tobacco cigarettes (TCs) are scarce. Ventricular repolarization in people who smoke TCs is abnormal. Baseline repolarization was compared among non-smokers, and people who use ECs or TCs. Then, the acute effects of ECs and TCs on metrics of ventricular repolarization, were compared in people who chronically smoke. A total of 110 participants(59 female), includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In our prior retrospective study, we reported a greater Tp‐e prolongation following acute TC smoking compared to EC use in the general population who smoke (Ip et al., 2020 ). In a prospective study comparing the acute effect of TCs and ECs on VR in the same individual, we found that ECs but not TCs significantly increased the Tp‐e interval following a provoked acute increase in heart rate (Ruedisueli et al., 2023 ). These findings are supported by preclinical studies in which acute exposure to aerosols generated from heating vegetable glycerin (VG) and/or propylene glycol (PG), both common EC liquid constituents, significantly prolonged ventricular repolarization in mice (Carll et al., 2022 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In our prior retrospective study, we reported a greater Tp‐e prolongation following acute TC smoking compared to EC use in the general population who smoke (Ip et al., 2020 ). In a prospective study comparing the acute effect of TCs and ECs on VR in the same individual, we found that ECs but not TCs significantly increased the Tp‐e interval following a provoked acute increase in heart rate (Ruedisueli et al., 2023 ). These findings are supported by preclinical studies in which acute exposure to aerosols generated from heating vegetable glycerin (VG) and/or propylene glycol (PG), both common EC liquid constituents, significantly prolonged ventricular repolarization in mice (Carll et al., 2022 ).…”
Section: Discussionmentioning
confidence: 95%
“…Several important points are worth emphasizing: First, although the increase in plasma nicotine was smaller following acute EC use compared to TC smoking, the increase was nonetheless significant. Second, the difference in nicotine levels occurred in PLWH despite using the same protocol we have used in many studies for many years, which, in the general adult population, reliably and consistently produced similar plasma nicotine levels as smoking one TC (Arastoo et al., 2020 ; Haptonstall et al., 2020 ; Nguyen et al., 2024 ; Ruedisueli et al., 2023 ). Potential explanations the difference in the current study include a possible interaction of HIV drugs or the HIV milieu that impacted metabolism of nicotine delivered by the EC device differently from the TC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation